Hybrid transistor manipulation controlled by light - Suwanpayak, Nathaporn; Teeka, Chat; Yupapin, Preecha P. (My University, 2011)
In this article, the novel type of transistor known as a hybrid transistor is proposed, in which all types of transistors can be formed by using a microring resonator called a PANDA microring resonator.In principle, such a transistor can be used to form for various transistor types by using the atom/molecule trapping tools, which is named by an optical tweezer, where, in application, all type of transistors, especially, molecule and photon transistors can be performed by using the trapping tools, which will be described in details. © 2011 Wiley Periodicals, Inc.
Keywords: hybrid transistor; molecular transistor; photon transistor; single electron transistor